Multimodal Meaning Making and Language Learning in Digital Multilingual Environments - Sinrang, Nurliana (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study investigates the role of multimodal learning tools in language acquisition within digital multilingual environments. The primary goal was to assess how learners engage with semiotic resources like text, images, audio, and video in enhancing language skills Subjects and Methods: A mixed-methods design was used, with quantitative data from pre- and post-tests measuring improvements in vocabulary, grammar, and speaking proficiency, and qualitative data from interviews and focus groups capturing learners’ perceptions and experiences. Results: The results indicated that learners using multimodal resources showed significant improvements in all language skills, especially in speaking proficiency. Vocabulary and grammar scores in the experimental group increased by 15% and 12%, respectively, while speaking skills saw a 20% improvement. Learners expressed positive perceptions of the multimodal tools, particularly video-based lessons and interactive exercises, though challenges related to platform navigation and cognitive overload were noted. The study concludes that multimodal learning tools are effective in enhancing language acquisition, but emphasizes the need for careful design to minimize challenges. Conclusions: Future research should explore ways to optimize digital tools for diverse learner needs, and further investigate the long-term impact of multimodal learning on language retention.